Does Gratitude Ensure Workplace Happiness Among University Teachers? Examining the Role of Social and Psychological Capital and Spiritual Climate - Garg, Naval; Mahipalan, Manju; Poulose, Shobitha; Burgess, John (Frontiers in Psychology, 2022)
The study examines the necessity and sufficiency of gratitude for supporting workplace happiness among Indian university teachers. It also explores the mediating effect of psychological capital and social capital in the relationship between gratitude and workplace happiness. The moderating effect of spiritual climate is investigated. A survey of 726 university staff in India was undertaken to examine the relationship between gratitude and workplace happiness. A series of statistical tests involving correlation, multiple regression, and necessary condition analysis was undertaken from the data set. The mediation effect of psychological capital and social capital was investigated using bootstrapping estimates using Hayes’s (2013) PROCESS Macro in SPSS. Also, the moderation effect of spiritual climate was explored using PROCESS Macro in SPSS. The results reveal that gratitude is both a sufficient and necessary condition for workplace happiness. It also suggests a significant mediating effect of psychological capital and social capital. Also, a significant effect of spiritual climate amid the relationship between gratitude and workplace happiness is concluded. The study is one of the first studies that explore the relationship between gratitude and workplace happiness. It examines the mechanism through which gratitude influences happiness in the workplace.